2002
DOI: 10.1021/ma020145l
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Curing of Aryl−Ethynyl End-Capped Polyimide Oligomers and Model Compounds:  A Kinetic Study Probing Substituent Effects

Abstract: phthalimide (1), N-phenyl-4-(4-methoxy-1-naphthylethynyl)phthalimide (2), and N-phenyl-4-(4-benzonitrileethynyl)phthalimide (3) were synthesized to probe the effect(s) of electronic subsituents on the thermal curing of aryl-ethynyl end-capped oligomers using end-cap model compounds. The curing kinetics were analyzed using SEC and NMR techniques and Arrhenius parameters were determined and compared to the anthracenyl, naphthyl, and phenyl analogues, 4, 5, and 6, respectively. A thermal curing rate acceleration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…However, more researchers have demonstrated the cure of ethynyl of PEPA would be promoted by electron-withdrawing groups attached to phenylethynyl or ethynyl moiety. By replacing the phenyl group attached to ethynyl moiety of PEPA with naphthyl or anthracenyl group could decrease the cure temperature by 30–80 °C [ 31 , 32 , 33 ]. Harris et al [ 34 ] reported that end groups derived from PEPA with electron-withdrawing attached to phenylethynyl moiety exhibited higher reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, more researchers have demonstrated the cure of ethynyl of PEPA would be promoted by electron-withdrawing groups attached to phenylethynyl or ethynyl moiety. By replacing the phenyl group attached to ethynyl moiety of PEPA with naphthyl or anthracenyl group could decrease the cure temperature by 30–80 °C [ 31 , 32 , 33 ]. Harris et al [ 34 ] reported that end groups derived from PEPA with electron-withdrawing attached to phenylethynyl moiety exhibited higher reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the cross-linking units, imide oligomers include phenylethynyl unit-based oligomers, ethynyl-based oligomers and nadic anhydrideterminated oligomers. Compared to the other thermosetting polyimides, phenylethynyl-terminated imide oligomers (PETIs) have received more attention, [6][7][8][9][10] because PETIs could undergo thermal curing without the evolution of volatile by-products, and the cured resins display high glass transition temperatures (T g s), excellent chemical resistance and better thermal oxidative stability. [11][12][13] Hence, PETIs have been employed as matrices to fabricate carbon fibrereinforced composites for high temperature applications.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal‐curing kinetic analysis of the oligomeric systems OI‐5 and OI‐6 were also carried out via DSC by monitoring the change in T g as a function of time at the various temperatures 350, 360, 370, and 380 °C. The extent of curing (x) was calculated by DiBenedetto equation modified for highly crosslinked networks according to the literatures 38–41, 45, 46. Applying first‐order data analysis (−ln(1 − x) = K t ), the rate constant ( K ) at certain temperature was obtained from the very good line fit.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, PETI‐5 was selected as the adhesive and composite matrix for the excellent mechanical properties and good processability 37. In recent years, Wright found that the curing rate increased in the order of phenylethynyl < naphthylethynyl < anthracenylethynyl in phthalimide model compound as well as the corresponding imide segment in PETI‐5 at the same temperature 38–41. Hergenrother prepared 4‐(2‐phenylethynyl)‐1, 8‐naphthalic anhydride (PENA) and 4‐(1‐naphthylethynyl)‐1, 8‐naphthalic anhydride (NENA), then studied the thermal and mechanical properties of imide oligomers terminated with these aryl ethynyls 36…”
Section: Introductionmentioning
confidence: 99%